Levisticum officinale extract protects against CCl4-induced hepatotoxicity through anti-inflammatory, anti-fibrotic, and antioxidant properties in rats - Nahid Ghaedi; Iran Pouraboli; Mansour Mirtadzadini; Mohammad-mehdi Moeini-aghtaie (Asian Pacific Journal of Tropical Biomedicine, 2024)
Objective: To investigate the hepatoprotective effects of Levisticum officinale extract on CCl4-induced hepatotoxicity. Methods: Different doses of Levisticum officinale extract were given orally to rats for 10 days, then rats received a single dose of CCl4 (2.5 mL/kg, 50% v/v in liquid paraffin). Biochemical and histopathological assays were performed to assess the effects of the extract on liver function and architecture. Moreover, antioxidant and oxidative markers as well as inflammatory and fibrotic indicators were measured. Results: Pretreatment with Levisticum officinale extract significantly mitigated CCl4-induced damage to liver structure, improved serum levels of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, urea, total bilirubin, and total protein, enhanced glutathione content and superoxide dismutase and catalase activities in the liver, as well as decreased plasma and hepatic malondialdehyde levels. Immunohistochemical results demonstrated that the extract reduced Ki-67 and α-SMA expression and Masson’s trichrome staining revealed decreased liver collagen in rats treated with Levisticum officinale extract. Moreover, Levisticum officinale extract markedly decreased the gene expressions of TNF-α, 1L-6, TGF-β1, MCP-1, and COX-2. Conclusions: Levisticum officinale extract exerts hepatoprotective effects on CCl4-induced hepatotoxicity through antioxidant, anti-inflammatory, and anti-fibrotic activities.